Validation of the Chronic Illness Adjustment Scale in Turkish patients with chronic disease - Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz; Ciftci, Bahar (Bmc, 2025)
Objective This study aimed to adapt the Chronic Illness Adjustment Scale into Turkish and to evaluate its validity and reliability in assessing how individuals with chronic illnesses adjust to their condition. Methods This methodological study was conducted between July 2024 and July 2025, involving 518 chronic patients who visited the internal medicine outpatient clinic of a university hospital. Data were collected using the Personal Information Form and the Chronic Illness Adjustment Scale (CIAS). Results According to confirmatory factor analysis, the factor loadings of the scale ranged from 0.300 to 0.850, and a five-dimensional structure was confirmed. The scale's fit indices were x(2) = 495.17, df = 140 (p < 0.05), x(2)/df = 3.53, RMSEA = 0.070, CFI = 0.94, SRMR = 0.057, TLI = 0.92, RMR = 0.044, and AIC = 652.03. The overall Cronbach's alpha coefficient of the scale was 0.80, and for the sub-dimensions, it ranged between 0.67 and 0.80. The validity and reliability of CIAS were proven without any changes to its original form. Conclusion This study determined that the adapted CIAS consists of five subscales and 19 items, is compatible with Turkish culture, and is a valid and reliable scale.
Keywords: Health problem; Chronic disease; Adaptation; Chronic Illness Adjustment Scale; Reliability; Validity; Turkey